A terrible structuralist wisdom: how language affects the identity of an emigrant. Case study based on the autobiography »Lost in translation« by Eva Hoffman - Szepe, Agata (Wydawnictwa AGH, 2013)
This essay is a case study about linguistic mechanisms that affect an emigrant's life. The research is based on the autobiography Lost in Translation by the Polish emigrant Eva Hoffman, analyzed with the use of theories of the structural linguistic school. According to the research, some linguistic rules influence her life very deeply. She communicates poorly because the expression of new language corresponds with different content from the native language, creating another form. Eva starts to treat daily communication like a written text, in the meaning used by Roland Barthes, which results in alienation. However, some linguistic principles such as the arbitrary nature of a sign or inseparability of signifiant and signifie do not affect her at all. She deepens her understanding of both her mother tongue and the new one by linguistic terms such as translation describing, defining and finding synonyms and tries to find her own identities using expressions such as I, you, here, near, and far, belonging to linguistic universals. Her identity is an identity-in-progress because she replaces her old home with a new center of the world. The old home remains a heterotopia while an emigrant changes her onceptions connected with the words here, there, near, and far.

Artykuł, opierając się na autobiografii Zagubione w przekładzie polskiej emigrantki, Eve Hoffman, analizuje mechanizmy językowe, które mają wpływ na życie emigranta. Eve trudniej się porozumiewać, ponieważ forma wyrażania nowego języka nie odpowiada formie treści języka rodzimego. Zaczyna traktować codzienną komunikację, jako tekst, w znaczeniu, używanym przez Rolanda Barthesa, co prowadzi do poczucia wyobcowania. Z drugiej strony, niektóre zasady językowe przestają ją obowiązywać. Jest to na przykład arbitralny związek znaczącego i znaczonego oraz zasada, mówiąca, że nie da się ich od siebie rozdzielić. Równocześnie, Hoffman pogłębia zrozumienie swojego i obcego języka przez posługiwanie się tłumaczeniem, definiowaniem i synonimami. Określa na nowo swoją tożsamość, używając wyrażeń, należących do uniwersaliów językowych. Tożsamość Eve jest niestabilna, ponieważ idea domu zostaje zastąpiony nowym, subiektywnym centrum świata. Poprzednie miejsce zamieszkania pozostaje heterotopią, a emigrant zmienia sposób widzenia świata, poprzez nadanie nowego znaczenia wyrażeniom: tutaj, tam, blisko, daleko.
Straszna mądrość strukturalisty: o językowej tożsamości emigranta
Studia Humanistyczne AGH
Keywords: emigrant; identity; language; emigrant; tożsamość; text; mechanizmy językowe; tekst; structuralism; strukturalizm